Education of Mexican Woman in the feminine press during the Porfiriato - Torres Aguilar, Morelos; Atilano Villegas, Ruth Yolanda (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article is the result of a research on Mexican publications aimed at women during the Porfiriato, which played an important educational function. The main objective of the research is to analyze, to understand, to compare and to interpret the main proposals showed in the publications regarding the women education, from editorial articles or highlighted columns. The research provides an overview that shows the most important positions in the debate raised in feminine education magazines. The method used was the review and analysis of the hemerography period in order to study different publications, based on the most representative there was a selection of ten. Subsequently it was applied a hermeneutical framework to analize, understand and then interpret the historical process, the educational discourse and the ideological content of the data media above. The research concludes that the educational content of the publications correspond to the concept of ‘informal education’; as well as there were two antagonistic points of view about women education, a conservative one recommending to educate them, and the liberal or modern one, which proposed to instruct them. In this sense, the main hypothesis is that both positions tried to determine, through education, the profile that the Mexican women should have at that time.